DIAGNOSTIC AND PROGNOSTIC SIGNIFICANCE OF THE MEASUREMENTS OF pH, pO2 AND pCO2 IN PERITONEAL FLUID COLLECTIONS. - Ömer ŞAKRAK; Fevzi KUŞ; Oktay BANLI; Nusret AKYÜREK; Yücel ARITAŞ; Yaşar YEŞİLKAYA (Turkish Journal of Gastroenterology, 2020)
-